1975
DOI: 10.1097/00000658-197509000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Host Resistance in Sepsis and Trauma

Abstract: Host resistance to infection was measured by the in vivo response to 5 delayed hypersensitivity antigens and to sensitivity and challenge by dinitrochlorobenzene (DNCB) in 55 seriously ill or injured patients and in 50 preoperative patients. A close correlation between infections, septicemia, death related to infection and anergy was found in the postoperative and post injury patients and was predictive of these complications in the patients studied preoperatively. Decreased body cell mass was noted in both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

1983
1983
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(65 citation statements)
references
References 31 publications
1
61
0
3
Order By: Relevance
“…This indicates that the endogenous CD4 ϩ population during sepsis does not play a major role in outcome, likely due to an already inherent dysfunction in the CD4 ϩ T cell population produced by sepsis. It is known that an increase in apoptotic death occurs in the CD4 ϩ T cell population during sepsis (34,35) and contributes to the anergy in the T cell compartment (36,37). Similar to this T cell anergy, we observed decreased effector cell function (proliferation to a mitogenic stimulus) in the CD4 ϩ CD25 Ϫ cell population isolated from spleens of septic animals compared with sham-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the endogenous CD4 ϩ population during sepsis does not play a major role in outcome, likely due to an already inherent dysfunction in the CD4 ϩ T cell population produced by sepsis. It is known that an increase in apoptotic death occurs in the CD4 ϩ T cell population during sepsis (34,35) and contributes to the anergy in the T cell compartment (36,37). Similar to this T cell anergy, we observed decreased effector cell function (proliferation to a mitogenic stimulus) in the CD4 ϩ CD25 Ϫ cell population isolated from spleens of septic animals compared with sham-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…In a seminal study by MacLean et al, 13 it was observed that septic patients and trauma patients that progressed to sepsis displayed an inability to develop delayed-type hypersensitivity responses. We initially used a standard system whereby we could test whether an adaptive T-cell-dependent immune response can develop in septic mice by immunizing subcutaneously with the T-cell-dependent antigen NP-KLH mixed with alum and examining antigen-specific antibody production.…”
Section: Sepsis Decreases T-cell-dependent Antibody Responsesmentioning
confidence: 99%
“…In trauma patients, inhibitory activities affecting neutrophil chemotaxis, lymphocyte reactivity, and neutrophil chemiluminescence have been identified in the sera. [39][40][41][42] The nature of the inhibitory activity in trauma patients' sera is at present unknown. It is not clear whether it is a newly synthesized product, a protein, or a substance of a different nature.…”
Section: Discussionmentioning
confidence: 99%